2021
DOI: 10.1002/nag.3282
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and implementation of an elastoplastic constitutive model for sand‐fines mixtures

Abstract: Sand‐fines mixtures are commonly used engineered materials, and their mechanical behavior is significantly affected by density, confining pressure, as well as fines content. Although many laboratory tests have been performed on sand‐fines mixtures, few works have been conducted on its constitutive law. To adequately describe the mechanical behavior of sand with different fines content, a novel elastoplastic constitutive model was developed for sand‐fines mixtures by incorporating an equivalent granular state p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Existing numerical implementation schemes of the constitutive models are generally classified as backward Euler 51 54 and forward Euler 55 57 schemes. The backward Euler scheme with the return-mapping technique is accurate because the resulting stress automatically satisfy the yield function to a specified tolerance.…”
Section: Constitutive Relation Of Casm-kiimentioning
confidence: 99%
“…Existing numerical implementation schemes of the constitutive models are generally classified as backward Euler 51 54 and forward Euler 55 57 schemes. The backward Euler scheme with the return-mapping technique is accurate because the resulting stress automatically satisfy the yield function to a specified tolerance.…”
Section: Constitutive Relation Of Casm-kiimentioning
confidence: 99%
“…In this flow regime, the rheological behavior and the constitutive law are dictated by the inertial number 6,33,55,57 . In geomechanics, constitutive modeling 58–60 for granular soil or rock becomes more complicate when considering loading path, 61–63 water content, 62,64 and particle breakages 40,58 …”
Section: Introductionmentioning
confidence: 99%
“…In this flow regime, the rheological behavior and the constitutive law are dictated by the inertial number. 6,33,55,57 In geomechanics, constitutive modeling [58][59][60] for granular soil or rock becomes more complicate when considering loading path, [61][62][63] water content, 62,64 and particle breakages. 40,58 Until now, most simulations for plane shear flow have focused mainly on the dimensional analysis and less on the velocity-stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…SRMs are widely encountered in geotechnical engineering, such as natural slopes [6], waste rocks and tailings from mining [8], clay-aggregate mixtures in rockfill dams [12] and tunnels [14]. The soil content (sc) is one of the most important factors governing the mechanical behavior of SRMs [3,26,29,33,36]. In recent years, many field tests, laboratory tests and numerical simulations have revealed that sc greatly affects the shear strength [4,16,23,37], failure modes [5,15,17], stress-dilatancy [4,33], and critical state parameters of SRMs [25,33].…”
Section: Introductionmentioning
confidence: 99%
“…Although some pioneering works has been done on the constitutive modelling of SRMs [7,17,26], properly modeling the behavior of this kind of complex heterogeneous materials remains an open challenge [35,39,40]. Predicting the mechanical properties SRMs for varying sc remains a widely open issue.…”
Section: Introductionmentioning
confidence: 99%